Application of the environmentally friendly technology for the removal of PCBs from mineral oils and power transformers to achieve very low values of PCBs for repair and materials recycling - Mihajlović, Draginja; Jankovic, Jelena; Vasović, Valentina; Ivančević, Vladimir; Lukić, Jelena (Proceedings, Electrical engineering institute "Nikola Tesla", 2022)
The Republic of Serbia signed and ratified the Stockholm Convention on Persistent Organic Pollutants. Law on ratification of the Stockholm Convention was adopted and actions were defined through the National Implementation Plan and the Action Plan. On their basis Project Proper Management and Final Disposal of Polychlorinated Biphenyls (PCBs) was created. Institute Nikola Tesla (INT) participated in the realization of the project. In the period from 2015 to 2022, 601 tons of PCB oil was successfully decontaminated by the INT mobile plant, i.e. the PCB content was below 50 mg/kg, which classified the power transformers (PT) as non-contaminated [1,2]. If PT becomes waste or in case of necessary repair or oil regeneration, the required limit value is 10 mg/kg. According to data from INT database there are still 2637 PTs containing PCBs in the concentration range of 2 to 50 mg/kg. In this paper application of the environmentally closed INT decontamination technology for achieving low values ​​of PCB in the oil is shown.
Keywords: power transformer, polychlorinated biphenyls (PCB), environmentaly closed, transformer repair, recycling